Pelatihan Standardisasi Juru Sembelih Halal (Juleha) Berbasis Fikih dan Animal Welfare - Ahmad Qusairi; Zainal Abidin; Abdurrahman Ahmad Agil; Deden Ramdhani; Nur Hanifansyah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2026)
Community-based qurban slaughtering practices still face challenges related to halal slaughter competency, animal welfare, and carcass hygiene. This community service program aims to improve participants' knowledge and skills through training in Islamic jurisprudence-based halal slaughtering, animal welfare, and hygienic carcass management. The program involved 65 participants consisting of mosque administrators, neighborhood qurban committees, and senior Dalwa students. The program evaluation approach utilized a pretest–posttest design, practical simulations, and observation of participant skills. Results showed an increase in the average knowledge score from 48.50 to 86.20 after training (p < 0.001). Ninety-two percent of participants were able to apply minimal-stress animal handling techniques, and 88% demonstrated humane animal restraint practices. The hanging skinning method and the use of a mechanical bone saw also supported more hygienic and efficient carcass handling. This program effectively strengthened safer, more humane, and more hygienic communal qurban management practices.